Memory-less Property of Distribution

By definition, memorylessness means the distribution of waiting time (in continuous case) or number of trials (in discrete case) does not depend on how much time has passed or how many trials you have tried. There are only two distributions are memoryless: exponential distribution in continuous case, and geometric distribution in discrete case. Actually geometric is analogous to exponential. Mathematically, memorylessness can be expressed as below where m and n are non-negative integers in discrete case, or non-negative real numbers in continuous case:
$$P(X \ge m+n | X \geq m) = P(X \ge n)$$
Using conditional probability, we can write left hand side to
$$ P(X \ge m+n | X \geq m) =  \frac {P( X \ge m+n, X \geq m)}{P(X \geq m)}$$
Since m and n are both non-negative, we can simplify the numerator as $P( X \ge m+n, X \geq m) = P(X \ge m+n)$, so above equation becomes
$$P(X \ge m+n | X \geq m) =  \frac {P( X \ge m+n)}{P(X \geq m)} $$

It is not hard to prove why exponential and geometric distributions are memoryless. We can just plug in the cdf and work it out. I will prove for the exponential distribution, and geometric distribution should be analogous to exponential distribution. As we know the cdf of exponential distribution is $F(x) = 1 - \lambda e^{- \lambda x}$, for $ x \geq 0$. We can then plug it in the above equation:
$$ P(X \ge m+n | X \geq m) =  \frac {P( X \ge m+n)}{P(X \geq m)} = \frac {e^{- \lambda (m+n)}} { e^{ - \lambda m} } = 1- (1 - e^{ - \lambda n})= 1-F(n) = P (X \geq n)$$

Exponential and geometric distributions are only memoryless distributions. We can prove it as below. First, we define a function $G(m) = P(X \ge m)$. From $\frac {P( X \ge m+n)}{P(X \geq m)} = P (X \geq n)$, we can easily see $G(m + n) = G(m)G(n)$. Let n = m, we can easily see $G(2m) = G(m)^2$, and $G(3m) = G(m + 2m)= G(m)G(2m) = G(m)^3$. To generalize, we can get $G(a*m)=G(m)^a$ a is an integer. From $G(2m) = G(m)^2$, if we substitute m with m/2, we can immediately get $G(m/2) = G(m)^{1/2}$. Similarly, from $G(a*m)=G(m)^a$, we can get $G(m/a) = G(m)^{1/a}$ a is an integer. Now we can further generalize this to apply to any rational number $a/b$ that $G((a/b)m) = G(m)^{a/b}$. In order to generalize this to all positive real numbers, we can take limit of a series rational numbers, and it will still hold. We can simplify and make m = 1, then rewrite it to base of e, so the equation becomes $G(a) = e^{a*ln(G(1))}$. Since $G()$ is a probability, so $G(1)$ is between 0 and 1, and $ln(G(1))$ is a negative real number. We can define $ln(G(1))$ as $-\lambda$. Now it is obvious $G(a)$ as a can take any real positive number is just the $1 - (1 - e^{- \lambda a})$, which is $1 - F(a)$ where $F$ is the cdf of exponential distribution. For geometric proof, when a only takes positive integers, $G(a) = G(1)^a = 1 - (1 - G(1)^a) = 1 - F(a)$, where $F$ is cdf of geometric distribution.

Comments

Popular posts from this blog

Perform efficient Latent Semantic Index using Python

SVM

Open Source to E-discovery